2010
DOI: 10.1093/intimm/dxq051
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 integrase-hydrolyzing IgM antibodies from sera of HIV-infected patients

Abstract: IgG abzymes (Abzs) with different catalytic activities are a distinctive feature of various autoimmune (AI) diseases. At the same time, data concerning IgMs with catalytic activities are very limited. Electrophoretically and immunologically homogeneous IgMs were isolated from the sera of acquired immunodeficiency syndrome (AIDS) patients by chromatography on several affinity sorbents. Several rigid criteria have been applied to show that the integrase (IN)-hydrolyzing activity is an intrinsic property of IgMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(142 citation statements)
references
References 50 publications
13
129
0
Order By: Relevance
“…However, iodoacetamide inhibited integrase hydrolyzing activities of all polyclonal IgG and IgM preparations from HIV/AIDS patients by 12-99% [97,98]. Proteolytic activities of three MLChs (18, 14, and 10) not inhibited by EDTA and PMSF were significantly suppressed by iodoacetamide, while there was no effect on the most of MLChs with metal-dependent and serinelike activities (for example, Figure 20C).…”
Section: Catalytic Antibodies In Norm and Systemic Lupus Erythematosusmentioning
confidence: 96%
See 1 more Smart Citation
“…However, iodoacetamide inhibited integrase hydrolyzing activities of all polyclonal IgG and IgM preparations from HIV/AIDS patients by 12-99% [97,98]. Proteolytic activities of three MLChs (18, 14, and 10) not inhibited by EDTA and PMSF were significantly suppressed by iodoacetamide, while there was no effect on the most of MLChs with metal-dependent and serinelike activities (for example, Figure 20C).…”
Section: Catalytic Antibodies In Norm and Systemic Lupus Erythematosusmentioning
confidence: 96%
“…In addition, a high metal-dependent MBP-hydrolyzing activity for MS IgGs [86] and caseinhydrolyzing of human milk sIgAs [96] were recently revealed. It was shown that antiintegrase IgGs and IgMs of HIV-infected patients can contain abzymes hydrolyzing viral integrase of four types, resembling serine, thiol, metal-dependent, and acidic proteases, the ratio of which may be individual for every AIDS patient [97,98].…”
Section: Lupus 70mentioning
confidence: 99%
“…Natural Abz purification is one of the most complicated aspects of their study; it was discussed in detail in review (Nevinsky et al, 2000 b ). I n s t u d y A b z s f r o m t h e s e r a o f H I V -i n fected patients, electrophoretically and immunologically homogeneous AIDS Ab fraction (pIgG+pIgM+pIgA) was first purified by chromatography of the serum proteins on Protein A-Sepharose under conditions that remove non-specifically bound proteins Baranova et al, 2009Baranova et al, , 2010. pIgMs were separated from pIgAs and pIgGs by FPLC gel filtration of the total Ab fraction on a Superdex 200 (Baranova et al, 2009(Baranova et al, , 2010.…”
Section: Catalytic Antibodies Of Hiv-infected Patientsmentioning
confidence: 99%
“…I n s t u d y A b z s f r o m t h e s e r a o f H I V -i n fected patients, electrophoretically and immunologically homogeneous AIDS Ab fraction (pIgG+pIgM+pIgA) was first purified by chromatography of the serum proteins on Protein A-Sepharose under conditions that remove non-specifically bound proteins Baranova et al, 2009Baranova et al, , 2010. pIgMs were separated from pIgAs and pIgGs by FPLC gel filtration of the total Ab fraction on a Superdex 200 (Baranova et al, 2009(Baranova et al, , 2010. The homogeneity of the 150 kDa IgG was confirmed by SDS-PAGE with silver staining, which showed a single band under nonreducing conditions and two bands corresponding to the H and L chains after reduction (Fig.…”
Section: Catalytic Antibodies Of Hiv-infected Patientsmentioning
confidence: 99%
See 1 more Smart Citation